Replicating a habitus: transplanting capital, habitus and doxa in a school start-up - Shaw, Garth (School of Education, 2020)
Schooling in South Africa still reflects the inequalities of apartheid. The majority of learners live in low socioeconomic contexts, and face challenges accessing ‘quality’ education, which is largely only available at expensive, fee charging schools. Even if poorer learners do gain access to these schools, which are in the minority, they are not always optimally supported nor understood in terms of their challenges at home or needs at school. One response to this dilemma, by the Western Cape Education Department, was to establish a school seeking to produce ‘quality’ education, but focused on the needs of poorer learners. The founding of this school is the focus of this study. Modelled on, and guided by an established, high performing and geographically proximate school, located in an affluent community, this ‘school planting intervention’ took place over a three year start-up period. Drawing on Pierre Bourdieu’s concepts of habitus, doxa, capital and field, this case study examines how the institutional habitus of the established school, its capitals, and its position in the field of education have impacted the establishment of the new school. The study draws on data gathered from extensive interviews with school managers, teachers, parents and learners at both schools. The research process has also been supplemented by a contextual grounding of the project, with the researcher positioned as an inside-researcher. The strategies of the school planting interaction are considered, and the responses of various groups within the new school interrogated. In doing so, this study examines the implicit assumptions in practices and arrangements that are considered to be exemplary in a high performing school, and the ways in which these relate to the different needs and experiences of middle class and working class learners. The study finds that, while there were practical benefits to providing systemic support to the new school, there was also a profound disjuncture between assumptions about what constitutes ‘good practice’, grounded in a middle class experience, and the needs and experiences of poorer learners.